Oxygen Effect in Annealing Process of Aluminium Doped Zinc Oxide Films - Astuti, Budi; ., Sugianto; Mahmudah, Siti Nor; Marwoto, Putut; Ariyanto, Didik; Wibowo, Edy (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
Al doped ZnO (ZnO:Al) thin films was grown on corning glass substrate using dc magnetron sputtering. ZnO:Al thin film grown with plasma power 40 watt and 500 mTorr argon pressure for 120 minutes. Film was grown annealed on oxygen atmosphere with different pressure for 20 minutes. The crystalline of ZnO:Al film deposited has an hexagonal structure. The crystallites preferred orientation shift gradually from (002) to (101) direction as the pressure of oxygen increases. Transmittance in the visible regions increases with increasing pressure of oxygen about 81,27%. The optical characterization indicated that the band gap shift toward lower energies with increasing pressure of oxygen.